2019
DOI: 10.7326/m19-1152
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Relating Health Care Provider Burnout and Quality of Care

Abstract: Background: Whether healthcare provider burnout contributes to lower quality of patient care is unclear.Purpose: To estimate the overall relationship between burnout and quality of care, and to evaluate if published studies provide exaggerated estimates of this relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
257
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 323 publications
(271 citation statements)
references
References 177 publications
9
257
1
4
Order By: Relevance
“…Burnout is found to be associated with hand hygiene, while the effect of workload and mental health is indirect in our study, which has been explored by previous ndings. Just as burnout is frequently associated with poor practice, communication, quality and safety in health care [4], the effect works in hand hygiene behavior similarly. And researchers indicated that burnout was an incremental predictor of nurses' self-reported adherence with infection control measures (covering hand hygiene) [23,24].…”
Section: Contributors Of Hand Hygiene Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Burnout is found to be associated with hand hygiene, while the effect of workload and mental health is indirect in our study, which has been explored by previous ndings. Just as burnout is frequently associated with poor practice, communication, quality and safety in health care [4], the effect works in hand hygiene behavior similarly. And researchers indicated that burnout was an incremental predictor of nurses' self-reported adherence with infection control measures (covering hand hygiene) [23,24].…”
Section: Contributors Of Hand Hygiene Behaviormentioning
confidence: 99%
“…These hazards, including pathogen exposure, higher workload, psychological distress and occupational burnout, lead to poor adherence to infection control, healthcare-associated infections, other adverse events, etc. [2][3][4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers found that negative aspects of ProQoL in HCWs are associated with the poor quality of care, including poor quality and safety measures and unprofessional behavior, etc. [12,13]. The compassion satisfaction means that individuals feel happy with the work and want to continue, and the worse compassion satisfaction were reported to reduce the standards of care [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…While natural disasters, such as Hurricane Katrina, demonstrated the effectiveness of short-term emergency planning (1), the COVID-19 pandemic poses unique long-term stressors and risks to clinicians' physical, mental, spiritual, and emotional well-being. Leaders and front-line clinicians need to proactively protect the well-being of themselves and their colleagues to avoid adverse outcomes for clinicians and adverse effects on quality of patient care (2). We provide practical suggestions to encourage a culture that will sustain the clinician workforce during the pandemic.…”
mentioning
confidence: 99%